Analisis Film Bayi Ajaib Karya Alim Sudio(Semiotika Charles Sanders Peirce): Analysis of Alim Sudio's Bayi Ajaib Movie (Charles Sanders Peirce Semiotics) - Maharani, Binta; Sumarti, Endang; Rachman, Anita Kurnia (Universitas Nusantara PGRI Kediri, 2024)
This research explored the semiotic representation of Javanese mysticism in Alim Sudio's film